Antisense Oligonucleotide-Based Therapy on miR-181a-5p Alleviates Cartilage Degradation of Temporomandibular Joint Osteoarthritis via Promoting SIRT1 - Qi, Hexu; Zhao, Zhenxing; Xu, Lin; Zhang, Yue; Li, Yifei; Xiao, Li; Li, Yu; Zhao, Zhihe; Fang, Jie (Frontiers in Pharmacology, 2022)
Temporomandibular joint osteoarthritis (TMJOA) condylar cartilage degeneration and abnormal subchondral bone pathological remodeling induce pain and joint dysfunction, and cartilage degeneration is considered irreversible. Very few therapeutic approaches are administrated in practice. Nucleotides have demonstrated considerable potential as a next generation medication, and they have been applied in several models of osteoarthritis. There is a need to establish an effective protocol for TMJOA gene therapy. In the current study unilateral anterior crossbite (UAC) surgery was used to simulate mechanical stress-induced TMJOA in mice. Degeneration of condylar cartilage and destruction of subchondral bone were observed in damaged joints, and miR-181a-5p was elevated in chondrocytes. Intra-articular injection of miR 181a-5p antisense oligonucleotide (ASO) could reduce the cartilage damage and alleviate UAC-induced TMJOA progression, but it did not restore injured subchondral bone. Mechanically, miR-181a-5p evidently targeted the 3’ untranslated region of Sirt1 directly, resulting in inhibition of silent information regulator 1 expression and promoting apoptosis by elevating p53-dependent signaling, indicating that miR181a-5p ASO promoted chondrocyte survival. The present study suggests that ASO-based gene therapy may be an effective TMJOA treatment.